PASAR MODAL SYARIAH PERSPEKTIF SHARIA COMPLIANCE DI ERA DISRUPTIVE INNOVATION - Mohd Zamzami, R; Amaliyah; Hakim, Abdurrahman (Asosiasi Dosen PTKIS Indonesia, 2021)
Investment is a form of commitment to be able to hold a number of funds with the aim of obtaining a number of benefits (profits) and benefits (benefits) in the future. However, there are still investments as a means of collecting funds from the public with products and business activities that do not comply with the standards of government regulations, and do not even meet sharia compliance standards. Sharia compliance, which is in accordance with sharia principles in investing, is important as a guide for the community. Investment activities explicitly or implicitly are contained in a number of verses of the Qur'an and the sunnah of the Prophet Muhammad. Where in every investment activity that does not contain elements of haram, gharar, maysir, usury, tadlis, talaqqī al-rukban, ghabn, darar, rishwah, immorality and zulm. Furthermore, the Islamic Capital Market, as one of the Islamic investment instruments, is experiencing significant growth. The current performance of the Islamic Capital Market is in dire need of sustainability investment efforts in dealing with various forms of disruptive innovation management that are increasingly developing with various flagship products and excellent services. The birth of disruptive innovation provides easy accessibility and relatively more affordable costs for the user community. On this side, disruptive innovation is a market development that has a good impact on society and an increase in economic value on the consumer and business side, this must also be in accordance with the values of compliance with sharia principles (sharia compliance).